The Images of Mary in the Majorcan Gothic: Typologies and Iconographic Variants - Cerdà Garriga, Magdalena (Eikón / Imago, 2013)
Marian iconography is one of the most copious representations of medieval art, especially in devotional sculpture of the late Middle Age. Based on an analysis of the surviving pieces of Marian statues of the Majorcan Gothic, a typological, stylistic and iconographic study of this art is provided, which is the clue to understand the scope of the Gothic art and further development of the visual arts in the island.